One‐Dimensional Molecular Metal Halide Materials: Structures, Properties, and Applications. Issue 4 (12th January 2021) - Rahaman, Md. Zahidur; Ge, Shuaipeng; Lin, Chun-Ho; Cui, Yimin; Wu, Tom
Abstract : Metal halides with low‐dimensional molecular structures are the rising stars in the horizon of functional materials research. Among them, 1D metal halide hybrids are very promising for future optoelectronic applications because of their unusual photophysical properties resulting from strong quantum confinement. In the past few years, besides lead‐based 1D metal halide hybrids, research has been extended to lead‐free organic and all‐inorganic metal halides. Due to near‐unity photoluminescence quantum yield and excellent structural stability, all‐inorganic 1D metal halides are suitable for environmentally friendly optoelectronic devices. Moreover, the distortion and connectivity mode of metal halide octahedra arouse the formation of self‐trapped excitons within 1D metal halides, thus endowing the materials with distinct optical properties. Recent investigations have revealed many exciting characteristics of this new class of materials, such as ferroelectricity, ferromagnetism, optical cooling, and so on. This perspective presents not only structure–property correlations and recent applications of 1D metal halides but also the existing challenges and future research directions. Abstract : Molecular 1D‐networked metal halides are large crystals formed with metal halide quantum wires that are separated by cationic lattices in bulk matrixes. Herein, the latest breakthroughs in understanding the fundamental properties of 1D metal halide materials as applied to various optoelectronic applications are reviewed. Finally, the existing challenges and outline for future research directions are offered.